Fixed-Length Lossy Compression in the Finite Blocklength Regime - Kostina, Victoria; Verdu, S. (IEEE transactions on information theory, 2012)
This paper studies the minimum achievable source coding rate as a function of blocklength n and probability ϵ that the distortion exceeds a given level d . Tight general achievability and converse bounds are derived that hold at arbitrary fixed blocklength. For stationary memoryless sources with separable distortion, the minimum rate achievable is shown to be closely approximated by R ( d ) + √ V ( d )/( n ) Q -1 (ϵ), where R ( d ) is the rate-distortion function, V ( d ) is the rate dispersion, a characteristic of the source which measures its stochastic variability, and Q -1 (·) is the inverse of the standard Gaussian complementary cumulative distribution function.